Implementasi Balanced Scorecard Dalam Perencanaan Strategi Bersaing Sebagai New Entrant (Studi Kasus Pada PT. Alisha Transindo Utama) - Ayu Anissa Nur Prafitri; Kesi Widjajanti (Ikatan Sarjana Ekonomi Indonesia Cabang Semarang, 2021)
This increase in freight forwarding and delivery service activities has made business actors interested in opening their own freight forwarding and delivery services which eventually became known as new entrants, namely creating a business similar to the current conditions and one of them is PT Alisha Transindo Utama. The purpose of this study is to obtain a competitive strategy so that the company remains superior and survives in a tight and competitive business competition and can anticipate various kinds of changes that may occur in the future using the Balanced Scorecard method. The research was conducted with a qualitative approach with a case study design at PT Alisha Transindo Utama directly where researchers interviewed informants from company management and collected company data related to 4 perspectives, namely financial, customer, internal business processes and learning and growth. The results obtained from this study are to produce strategic targets for PT Alisha Transindo Utama with the financial perspective as the first priority, the internal business process perspective as the second priority, the learning and growth perspective as the third priority and the customer perspective as the last priority.